Meneladani Sejarah Pendidikan Islam di Kesultanan Aceh - Fitri, Rika; Ertati, Ertati; Yetni, Sofya; Riantito, Syofia (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2023)
Managing Islamic education in madrasah and the role of the Education Council and School Committee in improving the quality of Islamic education are things that must be considered. This research aims to analyze the management model of Islamic education in madrasah. This research uses a qualitative type with descriptive methods. The research carried out was field research field research by collecting data using observation, interviews, and documentation. The results of the research found the importance of community empowerment in Islamic education, namely to increase the role of the community in planning, implementing, and evaluating the provision of education, stimulating changes in attitudes and perceptions of the community towards a sense of partnership and tolerance, supporting the community to take a clear role in education, encouraging the community to develop innovation. The strategy for Islamic education in facing change is to adapt to environmental changes, monitor the educational environment, and influence the environment. Encourage the participation of parents and the community in managing Islamic education, namely arousing attention to the role of the education council and school committee in improving the quality of Islamic education, namely in determining the vision, mission, strategy, goals, logo, song and school rules and carrying out other educational technical matters.